2003
DOI: 10.1002/ps.630
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of atrazine treatment on soil bacterial, fungal and atrazine‐degrading communities by quantitative competitive PCR

Abstract: We report the development of quantitative competitive (QC) PCR assays for quantifying the 16S, 18S ribosomal and atzC genes in nucleic acids directly extracted from soil. QC-PCR assays were standardised, calibrated and evaluated with an experimental study aiming to evaluate the impact of atrazine application on soil microflora. Comparison of QC-PCR 16S and 18S results with those of soil microbial biomass showed that, following atrazine application, the microbial biomass was not affected and that the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 40 publications
(42 reference statements)
3
17
0
Order By: Relevance
“…Previous studies have also shown conflicting results due to the difficulty in establishing the causeand-effect relationship between organic pollutants and enzyme activities (Accinelli et al, 2002;Haney et al, 2002). Atrazine, which is an inhibitor of photosynthesis, has been reported to strongly depress cyanobacteria, to transiently affect the soil fungal microflora and to alter the denitrifying microflora (Isakeit and Lockwood, 1990;Martin-Laurent et al, 2003). In this study bacterial, Gramnegative bacterial, Gram-positive bacterial and arbuscular mycorrhizal fungal community composition showed significant (P < 0.05) atrazine-induced changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown conflicting results due to the difficulty in establishing the causeand-effect relationship between organic pollutants and enzyme activities (Accinelli et al, 2002;Haney et al, 2002). Atrazine, which is an inhibitor of photosynthesis, has been reported to strongly depress cyanobacteria, to transiently affect the soil fungal microflora and to alter the denitrifying microflora (Isakeit and Lockwood, 1990;Martin-Laurent et al, 2003). In this study bacterial, Gramnegative bacterial, Gram-positive bacterial and arbuscular mycorrhizal fungal community composition showed significant (P < 0.05) atrazine-induced changes.…”
Section: Discussionmentioning
confidence: 99%
“…cPCR has been widely used in the medical diagnostics but has also found its application in environmental biotechnology. The use of cPCR with 16s rRNA gene or the biodegradative genes such as ammonia monooxygenase (amoA), atrazine (atzC), cadmium (cadA) as targets have been used in quantification of non-culturable bacteria as well as to assess population density in both pristine and contaminated soil environments (Ka et al 2001;Kurkela et al 1988;Martin-Laurent et al 2003;Oger et al 2001). Mesarch et al (2000) has demonstrated the usefulness of the cPCR for C23DO gene present in contaminated soil samples.…”
Section: Discussionmentioning
confidence: 99%
“…Human activity over the years has led to hydrocarbon contamination of the soils near active and abandoned research stations (Aislabie et al 1999;Martin-Laurent et al 2003;Saul et al 2005). Fuel storage and refueling of aircrafts and other vehicles has led to localized fuel spills on land.…”
Section: Introductionmentioning
confidence: 99%
“…To detect the genes involved in the s ‐triazine degradation we used primers specifically designed from conserved regions of the atzA, atzB, atzC, atzD, atzE, atzF and trzN genes (Fig 1). The sequences of these primers and the conditions to run the PCR reactions have been described previously 20, 21…”
Section: Methodsmentioning
confidence: 99%